A narrative review of e-health systems' evolution – evidence from a regional study - Kitanovikj, Bojan; Koteska, Bojana; Levkov, Nikola; Velinov, Goran; Chagoroska, Zaklina (Emerald Publishing Limited, 2024)
Purpose The growing implementation of electronic health (e-health) systems has raised the importance of analyzing how these systems have been implemented in diverse regions. By employing a contextual sensitive approach and social mechanism theory, this study aims to better understand the reasons for the success and failure of e-health initiatives in the ex-Yugoslav region and derive useful insights for policymakers. Design/methodology/approach We employ a narrative review process grounded in the social mechanism theory, extended with field experts’ review, to acquire state-of-the-art information. Findings Findings indicate that different e-health systems coexist and evolve in different contexts in different countries, with varying levels of success. The contextual differences shape the broader environment, affecting the level of preparedness and capability for e-health implementation. Top-down approaches dominate e-health implementation in most countries when it comes to design process features, and more developed countries do not rely on strong social mechanisms for implementing e-health due to the openness of their culture towards e-health innovations. Practical implications Analyzing the milestones, challenges and functionalities of e-health systems in the region of interest can assist policymakers, academics and practitioners in making informed decisions and recommendations to enhance future e-health implementation. Originality/value No known studies evaluated e-health initiatives in the former ex-Yugoslav countries holistically and evolutionarily in the form of a comprehensive regional study. Further, our research endeavor is contextually specific since the health systems of these countries in the past were tied together under the federative umbrella health system and then diverged in terms of e-health development.
Keywords: E-health; Social mechanism; Regional study; Narrative review